Analysis of Credit Access among Cassava Value Chain Actors in Benue State, Nigeria - Christopher, Ogbanje Elaigwu; Mary, Odah O; Mohammed, Yahaya A (Journal of Asian Scientific Research, 2019)
The study examined credit access among cassava value chain actors in Benue State, Nigeria. Stratified random sampling technique was used to select 230 respondents, comprising 138 producers, 40 processors and 52 marketers. Primary data were collected using structured questionnaires. While frequency distribution, mean standard deviation and coefficient of variation were used to realise the objectives, Kruskal-Wallis (H) and one-way analysis of variance were used to test hypotheses one and two, respectively, for the study. The result showed that processors had more access to credit (75.00 %), while marketers obtained more average credit amount (N69,519.00) than the other actors. Findings further showed that the Chi-square statistic (25.56) of Kruskal-Wallis (H) was statistically significant (p < 0.05), indicating that there was statiscally significant difference in access to credit among cassava value chain actors in the study area. The difference was favour of the processors. In addition, the F-statistic (8.06) of one-way analysis of variance was statistically significant (p < 0.05), indicating that there was statistically significant difference in the amount of credit obtained among actors in the value chain. The difference was in favour of the marketers. It was recommended that actors in cassava value chain should have the same level of access and amount of credit.